Multi-objective attendance and management information system using computer application in industry strip - Ahmed Hazim Alhilali; Nabeel Salih Ali; Mohammed Falih Kadhim; Basheer Al-Sadawi; Haider Alsharqi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Information technology has played a vital factor in a competitive advantage for various business firms recently. Hence, catching up Investment of IT in most of the traditional industries for competitiveness purposes due to the relationship between organizational performance and IT use. In this study, attendanceand management information system (AMIS) was presented in the industry field based on multi-modules. Modules are management information, time- scheduling and attendance, and employee self- service module. The system used VB.NET environment for programming perspective as well MS SQL server for database storage. The system is secure and robust recordkeeping, keep employee up to date via self- service access, easy to use (simplified) and powerful time and attendance, active work schedules to make an employee happy and keep workers in the loop, as well, review and exporting different reports for staff manager, supervisor, and employee such as absence, vacation, time-off, employee wages, and etc.